Use of marijuana in pharmacy students (2000-2005) - Kavalirova, Alena; Visnovsky, Peter (Biomedical papers, 2005)
In 2000-2005, a survey on the consumption of legal and illegal drugs of abuse was conducted in 1571 students of Faculty of Pharmacy in Hradec Kralove, Charles University in Prague. The availability of cannabis and the prevalence rates of its use in university students were investigated. A standardized anonymous questionnaire was employed for the survey. The average age of respondents was 20 years. The number of females was higher (82.8 %) than that of males. Marijuana was the most available and the most commonly used illegal drug of abuse in the group of pharmacy students. Its offer and the life-time prevalence increased over the 5 year period of the survey from 55.8 % to 72.9 % and from 30.3 % to 48.4 %, respectively. There was a predominance of the male users over the female ones, mainly in a category of high frequency of marijuana consumption ("used more than five times"). Almost three quarters of marijuana consumers admitted more than one experience with marijuana. Our data provide worrying statistics and support the need of continuous education also in university students to advise them on the risks of drug misuse.
Keywords: Marijuana/Cannabis/Drug abuse